(untitled) (INNOVATIVE ECONOMY, 2026)
Tkachenko A.M., Levchenko N.M. INNOVATIVE APPROACHES TO DEFINING THE ESSENCE OF LOGISTICS IN TRADE: FORMATION OF THE STAGES OF GOODS MOVEMENT IN DISTRIBUTION CHANNELS Purpose. The aim of the article is to advance the theoretical foundations of the essence of logistics in trade and substantiate a digitally integrated approach to the formation of the stages of goods movement within distribution channels. Methodology of research. The methodological framework of the study is based on systemic, process-oriented, structural and functional approaches. The research employed methods of analysis and synthesis to clarify the economic essence of logistics in trade; comparative analysis to evaluate distribution channels; the systematization method to develop a model of the stages of goods movement; and the tabular method to summarize and present the research findings. Findings. The study demonstrates that logistics in trade is transforming from an operational function into a strategic management instrument that ensures the integration of material, information, and financial flows. The essence of trade logistics has been refined and defined as an integrated system for managing material, information, and financial flows. The key stages of goods movement, ranging from demand generation to after-sales service, have been systematized. The role of distribution channels as a core component of the logistics system determining the efficiency of goods movement has been substantiated. The findings confirm that the implementation of innovative approaches contributes to the optimization of logistics costs, improvement of customer service quality, and enhancement of enterprise resilience in a dynamic business environment. Originality. The paper refines approaches to interpreting the essence of logistics in trade as an integrated system for managing material, information, and financial flows, and an additional stage in the movement of goods in trade logistics has been identified – digital coordination and analytical support – which, unlike existing scientific approaches, allows logistics to be viewed not only as a system of physical product movement, but as a comprehensive, digitally oriented data management platform that ensures improved quality of management decisions, rapid response to changes in the external environment, and coordinated actions of all participants in the logistics chain. Practical value. The results of the study can be applied by trading enterprises in designing effective distribution channels, improving logistics management systems, implementing digital tools for coordinating logistics flows, and enhancing the efficiency of interactions among supply chain participants. Key words: trade logistics, stages of goods movement, distribution channels, logistics processes, digitalization, supply chain management.